First report and injury of Delia sanctijacobi (Bigot, 1885) (Diptera: Anthomyiidae) on tomato crop in Brazil - Rodolfo V. Castilhos; Juracy C. Lins Junior; Janaína P. Santos; Lucas R. P. Gomes (Entomological Communications, 2024)
The root maggot fly, Delia sanctijacobi (Bigot, 1885) (Diptera: Anthomyiidae), is an emerging pest of many vegetables. In this note, we report for the first time the occurrence of D. sanctijacobi damaging the tomato (Solanum lycopersicum L.) culture in Brazil. The occurrence was recorded in a tomato field located in the municipality of Coronel Freitas, Santa Catarina. The damage was characterized by roots consumption, opening of galleries in the stem and plant stand reduction. The first detection of D. sanctijacobi on tomato in Brazil brings an alert to growers and the need of future research about population dynamics and development of management strategies for this species.